ON THE FOOD OF CHANOS CHANOS (FORSKAL) - Tampi, P.R.S. (Indian Journal of Fisheries, 2015)
During the last few years several observations have been reported, particularly from the East Asian countries, regarding the food of the milkfish and most of the existing information is reviewed in a paper by Schuster (1949). Abstracts of other publications on this subject are also available in the bibliography on Chanos culture prepared by him (1952 i). Excepting for Sunier (1922) in Java and Chacko (1945 and 1949) in India, observations by others seem to have been based mostly on fish reared in saltwater ponds for commercial purposes.